1995
DOI: 10.1084/jem.181.3.1217
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent protein kinase II downregulates both calcineurin and protein kinase C-mediated pathways for cytokine gene transcription in human T cells.

Abstract: Engagement of the T cell receptor for antigen activates phospholipase C resulting in an increase in intracellular free calcium concentration ([Ca2+]i) and activation of protein kinase C (PKC). Increased [Ca2+]i activates Ca2+/calmodulin-dependent kinases including the multifunctional Ca2+/calmodulin-dependent protein kinase II (CaM-K II), as well as calcineurin, a type 2B protein phosphatase. Recent studies have identified calcineurin as a key enzyme for interleukin (IL)-2 and IL-4 promoter activation. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…However, the strong inhibition of FcyRI mRNA expression by cAMP, which only partially blocked STAT activation, suggests that additional pathways may be inhibited. These results show that at least two distinct major cellular signaling pathways that can inhibit immune responses (29)(30)(31)(32), those involving the serine protein kinases, calmodulin kinase, and protein kinase A, can inhibit STAT DNA-binding activity, and inhibition has important functional consequences for the expression of IL-6 regulated genes.…”
Section: Methodsmentioning
confidence: 99%
“…However, the strong inhibition of FcyRI mRNA expression by cAMP, which only partially blocked STAT activation, suggests that additional pathways may be inhibited. These results show that at least two distinct major cellular signaling pathways that can inhibit immune responses (29)(30)(31)(32), those involving the serine protein kinases, calmodulin kinase, and protein kinase A, can inhibit STAT DNA-binding activity, and inhibition has important functional consequences for the expression of IL-6 regulated genes.…”
Section: Methodsmentioning
confidence: 99%
“…The functional relevance of this region is further supported by the recent identification of two intracellular proteins, namely, Tctex-1 and CaMK II␦ (31), which interact with a 33-aa peptide region containing T410 and T412. Tctex-1 is a dynein motor complex component (47), and CaMK II␦ is a serine/threonine kinase involved in IL-2 down-regulation (48), implying a role in CD5 internalization and negative signaling, respectively. Should these interactions be confirmed experimentally, it would be interesting to explore the role of the two threonines in the binding to Tctex-1 and CaMK II␦ (31).…”
Section: Figurementioning
confidence: 99%
“…However, little information is available regarding the expression and function of CaMKII in T cells. Previous studies showed that constitutively active CaMKII␥B, CaMKII␥B T287D, blocked IL-2 and IL-4 promoter activities in Jurkat T cells, suggesting a role of CaMKII␥B in regulation of cytokine production (20,21). We have found that transgenic mice expressing CaMKII␥B T287D showed enhanced T cell activation and an increase in the proportion of memory T cells (22).…”
mentioning
confidence: 58%
“…The transfection of Jurkat T cells with CaMKII␥B T287D inhibited IL-2 and IL-4 promoter activity, suggesting a role of CaMKII␥B in the induction of T cell anergy (20,21). In contrast, we previously showed that there was an augmented response and an increase in memory CD4 and CD8 T cells in CaMKII␥B T287D transgenic mice (22).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation